A New Approach on the Calculation of Line Width of Gaussian Line Spectra1 - Lazo, Pranvera; He, Xiwen; Shen, Hanxi (Asian Journal of Chemistry, 2010)
A new method for the rapid and precise calculation of line width of Gaussian lines spectra is presented. The atomic absorption lines in UV-vis region are Gaussian lines and their line width is given as a function of the ratio of intensity n = Io/Ia and wavenwnber (σ) of the line. The line widths of some pure absorption lines are calculated. The deviation of the calculated values from the measured one is calculated. It is very small in all cases of the observed elements, smaller than 5%.